Development of Non-Conventional Energy Based on Ocean Wave Energy from an Economic, Social, and Environmental Perspective - Ramadhan, Muh. Asyhari (Collaborate Engineering Daily Book Series, 2025)
The development of non-conventional energy is a key strategy in addressing the challenges of the global energy crisis, climate change, and the need for a sustainable energy system. One energy source with significant potential but not yet optimally utilized is ocean wave energy. Indonesia, as an archipelagic country with a long coastline, offers significant opportunities for developing this energy. This article comprehensively discusses the development of ocean wave energy as part of non-conventional energy, reviewing economic, social, and environmental aspects in an integrated manner. Economically, wave energy has the potential to become an alternative energy source that can reduce dependence on fossil fuels and open up new investment and job opportunities. Socially, this energy development can increase energy access in coastal areas and remote islands, while simultaneously encouraging local community empowerment. Environmentally, wave energy is relatively environmentally friendly due to its low carbon emissions, although it still requires proper management to minimize its impact on marine ecosystems. Using a descriptive-analytical approach, this article demonstrates that integrating economic, social, and environmental aspects is crucial to ensuring the success of wave energy development. Policy support, technological innovation, and collaboration among stakeholders are key factors in realizing a sustainable and inclusive energy system in the future.